Determination of contract base payments to feeder-pig finishers - Parcell, J.L.; Langemeier, Michael R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Risks associated with independent feeder-pig finishing have prompted finishers to seek alternative finishing and marketing methods. A means of reducing risk has developed through contract feeder-pig finishing. Research results indicated that slightly risk-averse finishers required contract base payments ranging from $11.00 to $30.00 per head. Strongly risk-averse finishers required contract base payments ranging from $8.50 to $19.00 per head. The lower end of the ranges is for a low-profit finisher. The upper end of the ranges is for a high-profit finisher.
Keywords: Swine; Risk management; Contract feeder-pig finishing